Digitalization of public administration in Russia: risks, casuses, problems - L. A. Vasilenko; V. V. Zotov (Цифровая социология)
The article is devoted to the deliberation of the processes of digitalization of the activities of the authorities in modern conditions. The purpose of this article is to open a discussion on the problems of introducing new information and telecommunication technologies and improving the efficiency of the public administration system. Based on the analysis of the experience of implementing digital technologies and platform solutions in the field of public administration, a substantial characteristic of the problems of digitalization of public administration has been given. The key issues that require attention when carrying out digitalization of public administration on the basis of SWOT-analysis in terms of identifying weak, problematic aspects of the activities of the authorities and threats arising from the modern state of the Russian society, have been defined. Highlighting the weaknesses of modern public administration, the authors drew attention to such aspects of this problem as: 1) realization of “digitalization for the purpose of digitalization”; 2) deficiency of the required legal regulatory framework; 3) inefficiency of electronic document workflow, including problems caused by imperfections of the interface of reporting interactive forms, frequent change of the composition of indicators in reporting forms, desire of higher authorities to solve the problem of input of volume primary data at the expense of lower hierarchical levels; 4) absence of data analysis infrastructure, including due to imperfections of organization of interaction between agencies and incompatibility of information resources; 5) lack of data analysts and deficiency of necessary digital competences among state and municipal employees. Considering the threats and risks to the public administration system, the authors highlighted such aspects generated by the state of Russian society as: 1) creating a system of digital bureaucracy, 2) maintaining information and digital inequality, 3) insufficient knowledge and skills of citizens in the field of digital technologies, 4) reducing the publicity of the system of state and municipal administration. In the conclusion of the article it has been emphasized that the given facts are not unambiguously negatively interpreted, but it would be inexcusable to ignore even a small amount of them. It has been proposed to conduct a large-scale study that combines self-analysis of the processes of digitalization by authorities, a sociological study based on expert and mass surveys, an Internet survey.